2003
DOI: 10.1046/j.1472-765x.2003.01371.x
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of aerobic bacterial flora during Miso fermentation

Abstract: Aims: This article reports a microbiological study of aerobic mesophilic bacteria that are present during the fermentation process of Miso. Methods and Results: Aerobic bacteria were enumerated and isolated from Miso during fermentation and divided into nine groups using traditional phenotypic tests. The strains were identified by biochemical analysis and 16S rRNA sequence analysis. They were identified as Bacillus subtilis, B. amyloliquefaciens, Kocuria kristinae, Staphylococcus gallinarum and S. kloosii. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 9 publications
4
26
0
Order By: Relevance
“…DGGE analysis showed that microorganisms in the raw rice‐straw and Chungkookjang had greater bacterial diversity than revealed by a traditional culture‐based method. This result is consistent with those of Onda and others (2003) who explained that these limitations are likely due to the use of culture medium and the isolation of strains from high dilution plates. The common bands revealed that the bacterial species of Chungkookjang were derived from those of rice‐straw.…”
Section: Resultssupporting
confidence: 92%
“…DGGE analysis showed that microorganisms in the raw rice‐straw and Chungkookjang had greater bacterial diversity than revealed by a traditional culture‐based method. This result is consistent with those of Onda and others (2003) who explained that these limitations are likely due to the use of culture medium and the isolation of strains from high dilution plates. The common bands revealed that the bacterial species of Chungkookjang were derived from those of rice‐straw.…”
Section: Resultssupporting
confidence: 92%
“…; 4.65 × 10 6 MPM g −1 ), and Group C (the other Firmicutes; 3.7 × 10 6 MPM g −1 ) (Table 2, Figure 1). Number of Group A was similar level as those reports, in which B. subtilis originated from soybean was present at 10 4 ~ 10 6 CFU g −1 during miso fermentation, and decreased to under 10 4 ~ 10 5 CFU g −1 [28] [29]. Because of the difference of used incubation medium, total bacterial number in komekoujimiso (K) in this study was higher than that of the former study using MRS medium for lactic acid bacteria [27], and lactic acid bacteria was not detected in this study ( Table 2).…”
Section: Enumeration Of Each Prokaryotic and Eukaryotic Microbial Grosupporting
confidence: 88%
“…It has been reported that nisin biosynthesis occurs during the exponential growth phase affected by several cultural and environmental factors (1,23,26). Additionally, a dramatic decline of activity at the final stages of exponential growth phase was demonstrated for nisin and some other bacteriocins (1,10,22,32,33). As a result, investigating the metabolic features of bacteriocin biosynthesis and understanding the most effective factors on bacteriocin production is significant in order to improve the production rate.…”
Section: Introductionmentioning
confidence: 99%